Prevalence of Sexually Transmitted Infections and its Associated factors among women living with HIV/AIDS - Alvi, Yasir; Khalique, Najam; Ahmad, Anees; ., Urfi (Indian Journal of Community Health, 2019)
Background: Sexually transmitted infections (STIs) are significant public health problem in India. Studies have shown a considerably higher prevalence of STIs among females as well as in high-risk groups. Thus, we conducted this study to estimate the prevalence of STIs and to find out its associated factors among women living with HIV/AIDS. Material & Methods: A cross-sectional study was conducted at the ART centre, Aligarh. A total of 170 HIV positive women were approached with study tools comprising of pre-structured proforma. NACO STIs Syndromes were used to estimate STIs. Data was analyzed using the SPSS version 20.0, keeping significance at p<0.05. Results: We found the self-reported prevalence of STIs in HIV positive women to be 18.2% (31/170) at the time of interview and 49.4% (84/170) ever since the diagnosis of HIV. Most of the HIV women were presently having vaginal/cervical or urethral discharge syndrome (93.5%) and genital ulcer syndrome (16.1%). STIs were significantly associated with uneducated females and with irregular use of condoms. Conclusion: This study found the prevalence of STIs to be still higher among HIV positive women, in spite of years of targeted interventions reducing it. A proper action and further researches are required to explore and manage variables associating STIs for reducing its prevalence